Fire Carbon Cycle Research Is on the Rise: A Bibliometric Analysis from 1989–2023 - Di Wang; Siquan Yang; Qichao Yao; Weikang Zhang; Zhaogang Liu; Yanyan Pei; Fenglin Zuo (Fire)
Understanding how fires impact the carbon cycle is crucial for developing effective climate change adaptation and mitigation strategies. Although there is a substantial global body of research on fire carbon cycle (FCC), there are relatively few studies offering graphical and quantitative analyses. To assess the trends in FCC research from 1989 to 2023, we performed a bibliometric analysis using the Science Citation Index—Expanded database. A total of 2408 publications were analyzed in this study. The results revealed that from 1989 to 2023, the quantity of publications in the field of FCC studies increased significantly. However, the average number of citations per paper per year first increased rapidly, followed by a slow increase, and then a decline. The top 10 institutions contributing to FCC research were predominantly based in the United States and the United Kingdom, with these countries also leading in the number of publications and citations. Beyond the keywords “fire” and “carbon” used in collecting literature, “climate-change” and “dynamic” were the top two most prominent research focuses. The topic of research has shifted from 1989 to 2023. Climate, vegetation, and emissions were the basic themes, which were important but not well developed, and will be the focus of future research. Along with climate change, research will focus more and more on fire emissions and modeling.